2019
DOI: 10.20535/ibb.2019.3.4.183207
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Lemnoideae Species for Phytoremediation of Fresh Water with Elevated Manganese Concentration

Abstract: Background. Wastewater treatment using physical, chemical, and biological methods is primary solution for the reduction of water pollution that reaching the critical thresholds. The members of subfamily Lemnoideae, commonly called duckweed, are considered the most efficient aquatic plants for wastewater remediation. Although properties of duckweed to survive in water with high concentration of heavy metal ions such as chromium, cobalt, lead, nickel and cuprum are well documented, the growth of duckweed in wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…B, Cu, Fe, and Zn typically showed one order of magnitude higher range of BCF (~800–5700) compared to K, Na, Ca, and Mg, while the highest BCF in all the tested species was calculated for Mn (BCF = ~7500–15000, Figure 4 ). Duckweeds have long been known to efficiently accumulate various trace elements [ 2 , 50 ], and particularly high bioaccumulation capability was reported, amongst others, for B, Cu, Zn, and Mn [ 8 , 11 , 15 , 41 , 51 , 52 , 53 ]. Our data are in line with those observations and indicate that in the applied Steinberg medium, Mn was by far the most efficiently incorporated essential metal ( Figure 4 and Table S4 ), explaining its rapid decline in the medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B, Cu, Fe, and Zn typically showed one order of magnitude higher range of BCF (~800–5700) compared to K, Na, Ca, and Mg, while the highest BCF in all the tested species was calculated for Mn (BCF = ~7500–15000, Figure 4 ). Duckweeds have long been known to efficiently accumulate various trace elements [ 2 , 50 ], and particularly high bioaccumulation capability was reported, amongst others, for B, Cu, Zn, and Mn [ 8 , 11 , 15 , 41 , 51 , 52 , 53 ]. Our data are in line with those observations and indicate that in the applied Steinberg medium, Mn was by far the most efficiently incorporated essential metal ( Figure 4 and Table S4 ), explaining its rapid decline in the medium.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, selection and matching of the most suitable species for any given application can be crucial. For example, pertaining to metal accumulation, the high affinity of a particular species to a particular trace element can be either advantageous in remediating polluted waters, e.g., [ 15 ], or a disadvantage if duckweed is produced for use in feed or food, e.g., [ 16 ]. Further, a high metal bioaccumulation rate may not involve high tolerance to the same element that potentially limit the usefulness of certain species in some applications.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that the extend on Mn toxicity in four aquatic species of duckweed (Lemnaceae) depends on the source and concentration of nitrogen in the cultivation medium [ 43 ]. In particular, in great duckweed, Spirodela polyrhiza , the first characteristic symptoms of Mn stress appeared in form of characteristic brown spots when concentration of Mn was 40 mg/L (0.73 mM); however, the symptoms were largely reduced by the presence of ammonium in the medium in addition to nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to rice growing on paddy fields [ 5 , 7 ], aquatic duckweeds have clear bias for ammonium as a source of nitrogen when given a choice between ammonium and nitrate [ 42 ]. In our previous study [ 43 ], we have demonstrated that great duckweed, Spirodela polyrhiza , is sensible to Mn toxicity and manifests characteristic symptoms of Mn stress when concentrations of Mn exceed 40 mg/L (0.73 mM).…”
Section: Introductionmentioning
confidence: 99%
“…An environmentally friendly and economical treatment technology for the remediation of wastewater polluted with heavy metals is needed [ 114 ]. Duckweeds are relatively tolerant to heavy metals and able to take up many heavy metal ions, including those of cadmium, chromium, copper, iron, mercury, manganese, nickel, palladium, lead, and zinc [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. Therefore, duckweed also has potential uses for monitoring and remediating heavy metals [ 125 ].…”
Section: Duckweeds For Remediating Water Contaminated With Heavy Meta...mentioning
confidence: 99%